O PSC E A NOÇÃO DE “FAMÍLIA TRADICIONAL” COMO IDENTIDADE PARTIDÁRIA E RELIGIOSA: ANÁLISE DO PROCESSO ELEITORAL DE 2014 - SANTOS, EDER WILLIAM DOS (2016)
The present thesis analysis of how the Social Christian Party(PSC), overtime, appropriates itself of the religious identity of its political actorsmost of whom are members of the Evangelical Parliamentary Front, which defends in public the "traditional family", to the detriment of the plurality of family arrangements in the contemporary world. To make the object explicit - "traditional family" and PSC –, it was necessary to go back in time and research about the evangelical insert beginnings in Brazilian politics history.Therefore, weanalyzed the involvementof evangelical participation in the respective periods of Brazil: Colony, Empire and Republic. The difficulty that the evangelical people had to get in or to participate in partisan politics, among other factors, was due to the influence of Catholicism in the state. Therefore, we’ve looked up all the Constitutions (1824, 1891, 1934, 1937, 1946, 1967, 1969 and 1988) which say somethingin regards tothe prohibition and religious freedom in the country. So, we verified that in the period of Vargas and Populist Republic, a transitionfrom apolitical to politicism took place with intensity among Brazilian evangelicals however, they didn’t receive a formal support from their churches. Then the involvement of evangelicals in the political area during the military dictatorship was investigated with an emphasis on the vanguardpositioning IECLB, through the Curitiba Manifesto and also with the presence of evangelical parliamentarians in national Congress. The Pentecostal politicization is emphasized in our work, by pioneering nature of Manoelde Mello, and later in Redemocratization when evangelical institutions have organized to elect their candidates to the National Constituent Assembly. And with the end of military rule, the PSC arose as a political organization "nanico", however, it leaves the anonymity and gains visibility at media, when the minister and deputy (representative), Marco Feliciano, took the chair of the Human Rights and Minorities Commission in 2013. This is the historical background that projected the PSC and its actorsin the 2014 election with the slogan "traditional family."